OBSERVATION AND MITIGATION OF POWER TRANSIENTS IN 160GBPS OPTICAL BACKHAUL NETWORKS - Sharma, Vikrant; Sharma, Anurag; Kaur, Dalveer (European Scientific Journal, ESJ, 2014)
Erbium doped fiber amplifiers (EDFA) are most commonly used in optical networks for the most assorted applications. In this paper we have investigated the power transient effect of the cascaded erbium-doped fiber amplifiers (EDFA) in dense wavelength optical ring networks. The result shows, the power transient effect of EDFAs when channels are changed due to failure or channel reconfiguration. And also ring laser configuration technique has been reported to mitigate the effect of power transients.